A critical analysis of airline safety management with reference to pilots and aviation authority officers - Ho, Li-Chi (Cranfield University, 1996)
When we consider regional differences in air safety, a call for regional solutions is needed. This research probes the current situation in Taiwan and part of Asia from a regional perspective, aiming to better understand safety management in this region. Data was drawn from an extensive survey involving both airline pilots and aviation authority officers. The research investigated respondents' perceptions in airline safety management, and examined at their opinions about the role of aviation regulatory authorities and language disadvantages when exchanging safety information. The results demonstrated that there were key differences between the Captains and the First Officers surveyed in many aspects of airline safety management. The First Officers were more eager to have a blame-free and information-shared culture in current bureaucratic systems than were the Captains. Most pilots expected airline top management and aviation regulatory authorities to take more information responsibility for circulating safety related messages and information. It is believed that a confidential incident reporting system is one of the most appropriate tools for improving safety. It would be sensitive enough to provide early identification and warning for rooting out underlying causal factors, and allow constant tracking of hazards and evaluation of risks they involve. Hence, the second part of the thesis discusses the feasibility of establishing a national-level confidential incident reporting system in Taiwan from the viewpoints of the airline pilots and the air traffic controllers. The survey showed that there was great expectation for the introduction of a national- level confidential reporting system. However, there was need to undertake a high profile promotional period within the aviation community, followed by a two-year trial period. This would help to motivate potential reporters, eliminate their fear of punitive action, and enable consensus and support to be sought from the airlines. Initially, it is advised to begin with the participant of flight crew and air traffic controllers only. At the end of the trial period, an evaluation of the system achievements was recommended. After two years of successful operation the system might be extended to include maintenance personnel, cabin crews and other relevant parties.